Review paperCommissioning and periodic tests of the Esteya® electronic brachytherapy system - Candela-Juan, Cristian; Niatsetski, Yury; Ouhib, Zoubir; Ballester, Facundo; Vijande, Javier; Perez-Calatayud, Jose (Journal of Contemporary Brachytherapy, 2015)
A new electronic brachytherapy unit from Elekta, called Esteya®, has recently been introduced to the market. As a part of the standards in radiation oncology, an acceptance testing and commissioning must be performed prior to treatment of the first patient. In addition, a quality assurance program should be implemented. A complete commissioning and periodic testing of the Esteya® device using the American Association of Physicists in Medicine (AAPM), Groupe Européen de Curiethérapie and the European Society for Radiotherapy & Oncology (GEC-ESTRO) guidelines for linacs and brachytherapy units as well as our personal experience is described in this paper. In addition to the methodology, recommendations on equipment required for each test are provided, taking into consideration their availability and traceability of the detectors. Finally, tolerance levels for all the tests are provided, and a specific frequency for each test is suggested.